(untitled) (Studia Prawnicze / The Legal Studies, 1963)
Origin, goals and duties of the Council. In the first years after the Second World War the economic relations between the newly created socialist states did not differ essentially from the economic relations between the capitalist states. The legal basis for this relationship was established by bilateral agreements. As the economies of individual socialist countries developed, the need for closer ties of mutual economic cooperation became apparent. In 1949, the Council for Mutual Economic Assistance was established. The policy of economic discrimination by the capitalist states against the socialist countries was the additional factor that accelerated the formation of the said Council. The Statute of the Council of 1959 defines, on various levels, the multiple goals of this organization, without distinguishing any primary goal. Simultaneously with the tendencies to strengthen the importance and authority of the Council – as well as the tightening of economic cooperation – the member states declared themselves in favour of the maintenance and expansion of economic relations with the capitalist states. The goals and tasks of the Council cannot be treated in a static way; they were evaluated according to the economic development of the member states. In recent years, the basic approach to the activity of the Council has been the direct coordination of their economic plans. In view of this, it is necessary to establish a collective development plan for all the member countries of the Council. Specialisation and international cooperation, especially in the field of the machine industry, are of great importance for the economic cooperation of the Council members. Principles governing the Statute of the Council. Among the principles of the Statute, the principle of sovereignty is at the forefront. It means, in practice, that all resolutions are undertaken unanimously by the organs of the Council, and precisely with the consent of the states concerned. The economic cooperation of the Member States is at the same time based on mutual benefits. In particular, it relates to the equivalence of trade in goods between these states. In order to best determine the character of the mutual economic relations of the Member States, the principle of mutual fraternal assistance between them has a special significance. Since it is the basic principle of the new type of international legal relations, in the legal sphere it represents a manifestation of socialist internationalism. However, the authors disagree with the view of certain jurists in the field of socialist literature on international law, who consider the very principle of socialist internationalism to be a principle of international law. The principle of mutual fraternal assistance consists of free and mutual help. The bodies and competences of the Council. The structure of the Council has been designed to ensure that the tasks and goals undertaken by the organisation are carried out effectively. This chapter contains a detailed analysis of the Council’s bodies: the Council Session, the Executive Committee, the Standing Committees, the Secretariat, and the competences of these bodies. The important role now played (formed in June 1962) by a new body – the Executive Committee – in place of the Conference of Representatives of the Member States, and the diminishing role of the Council Session, have been particularly emphasised. Legal nature of the Council’s resolutions. Resolutions of the Council bodies can be taken as recommendations and decisions. The recommendations concerning economic, scientific and technical cooperation become binding on the States to which they are addressed only after their ratification by the competent bodies of those States. Decisions taken on organisational and procedural matters come into force from the moment of signing the minutes of the meeting of the given Council body. The authors carefully analyse the character and legal consequences of the recommendations. Some of them, due to their legal form, can be treated as sui generis reciprocal agreements between the States that these recommendations concern. However, these recommendations to the states concerned become the premises for the conclusion of formal international bilateral or multilateral agreements, in which these recommendations are directly implemented. Examples of such agreements follow. The final part of the chapter analyses the importance of the resolutions of the conferences of the representatives of the communist and workers’ parties for the activity of the Council. These resolutions mostly take the form of recommendations to the Council bodies. Although these recommendations are not legal acts and are not legally binding, they are of great importance to the Council as policy guidelines. Problem of international legal subjectivity of the Council. Being an international, non-exclusive organization, the Council nevertheless has a distinctly socialist character. It seems that in practice only socialist states could have full membership rights in the Council. However, it is possible that some non-socialist states, especially from the group of uncommitted states, may join the Council as “associate” members. The authors prove the unfoundedness of the claims of some bourgeois authors who impute to the Council the features of a “supra-national” organization. In the final part of the chapter, the authors consider the problem of the Council’s international legal subjectivity. The analysis of the Statute resolutions shows that the Council has ius contrahendi and enjoys certain privileges and immunities (organisation as such and its officials). In relation to what has been said, the thesis that the Council is a subject of international law seems to be justified.